The Influence of Work-Life Balance and Transformational Leadership on Organizational Commitment with Job Satisfaction as an Intervening Variable - Ahmad, Ahmad; Kirana, Kusuma Chandra; Subiyanto, Didik (JURNAL MANAJEMEN MOTIVASI, 2025)
Organizational commitment is identified as a psychological attitude that enables employees to recognize the goals and ideals of the organization. This commitment can be achieved when there is a balance between work and family, as well as the presence of transformational leadership. This study aims to identify the influence of work-life balance and transformational leadership on organizational commitment, mediated by job satisfaction. The research investigates and analyzes the effects of work-life balance and transformational leadership on organizational commitment, with job satisfaction as an intervening variable. The study employs a quantitative approach with a population of 76 agents. Primary data were collected through questionnaires and analyzed using SPSS and inferential methods, specifically Partial Least Squares (PLS) and variance-based Structural Equation Modeling (SEM), using SmartPLS 3 software. Four types of tests were conducted: indicator test, model fit test, hypothesis testing, and mediation analysis. The results indicate that work-life balance does not have a positive effect on organizational commitment; transformational leadership also does not directly influence organizational commitment. Additionally, work-life balance does not affect job satisfaction, whereas transformational leadership has a positive influence on job satisfaction. Furthermore, job satisfaction positively influences organizational commitment. Mediation analysis reveals that job satisfaction does not mediate the relationship between work-life balance and organizational commitment, but it does mediate the effect of transformational leadership on organizational commitment